Competitive athletes with femoroacetabular impingement and painful internal snapping treated arthroscopically with intrabursal iliopsoas fractional lengthening: High rate of return to sport and favorable midterm functional outcomes - Jimenez, A. E.; George, T.; Lee, M. S.; Owens, J. S.; Maldonado, D. R.; Paraschos, O. A.; Lall, A. C.; Domb, B. G. (The American Journal of Sports Medicine, 2022)
Background: Athletes with femoroacetabular impingement syndrome (FAIS) who undergo hip arthroscopy with iliopsoas fractional lengthening (IFL) in the context of painful internal snapping have demonstrated favorable patient-reported outcomes (PROs), return to sport (RTS), and resolution of internal snapping symptoms at short term follow-up. Midterm outcomes have not been established.